Primary extracranial nasopharyngeal meningioma in a dog. Issue 2 (16th April 2018) - Fauchon, Emilie; Husson, Jean‐Charles; Hernandez, Juan; Gomes, Eymeric
Abstract: An 8‐year‐old Labrador Retriever was presented for inspiratory efforts with stertor. A rhinoscopy and a magnetic resonance imaging scan were performed and revealed a naso‐pharyngeal mass. The mass was identified in the nasopharynx without meningeal extension. This mass was both T1‐ and T2‐hyperintense, compared to normal brain parenchyma without significant postcontrast enhancement. The mass was surgically removed and the histologic diagnosis was a mesenchymal tumor. Immunohistochemistry with antibodies was conducted and consistent with an extracranial meningioma. To the authors' knowledge, this is the first case report documenting a primary extracranial nasopharyngeal meningioma in a dog.